“I Wish I Had Help Earlier. We Could Have Been Happier Sooner.” Overcoming the Bystander Effect in the Care for Alcohol-Dependent Parents - Snoek, Anke; Dijkstra, Boukje A. G.; Markus, Wiebren; Van der Meer, Margreet; De Wert, Guido; Horstkötter, Dorothee (Frontiers in Psychology, 2021)
Parental alcohol dependency is associated with risks for the wellbeing of their children. However, guiding these families to support is often complicated. We interviewed 10 alcohol dependent parents, and held 3 focus group interviews with child welfare social workers, and alcohol and other drug workers. We identified a reluctance to act among professional and non-professional bystanders. Family members, neighbours, teachers, and general practitioners are often aware of parental drinking problems, but are reluctant to discuss them with the parents or to alert services designed to support families. The aim of this paper is to share the experiences of parents and show that parents appreciate interventions if done in a certain manner. Although parents were reluctant to discuss their drinking problem, they considered these problems as symptoms of underlying severe distress. They were highly motivated to get help for these underlying problems and wondered why they were not questioned about their distress by those around them. The silence of others reinforced pre-existing feelings of worthlessness and hopelessness. In this paper we analyse other’s hesitation to intervene as a form of the bystander effect, and make suggestions on how this bystander effect can be overcome.